The gendered realities and talent management imperatives of women physicians. Issue 3 (July 2016) - Hoff, Timothy; Scott, Sarah
Abstract : Introduction: U.S. medicine is increasingly a gender-balanced profession with half of all medical school graduates now female. Despite this reality and the potentially transformative nature of a large female physician cohort in U.S. health care, there is less examination of their workplace realities and the key talent management strategies for health care organizations employing women physicians. Purpose: First, we identify current knowledge about U.S. women physician satisfaction, role challenges, and work tradeoffs. Gender theory is used to help interpret these workplace realities. Second, we use this information to identify talent management strategies health care organizations might consider to mitigate the realities and provide greater support for women physicians. Methods: To facilitate our analysis, we conducted a narrative review of published research that includes analysis focused on U.S. women physicians for the time period 2006–2014. Applying ideas from gender theory, we extrapolated key findings from that research related to three issues: satisfaction, role challenges, and tradeoffs. Then we synthesized the findings to identify general talent management strategies that could address these dynamics proactively while enhancing recruitment and retention with respect to women physicians. Findings: U.S. women physicians express strong levels of satisfaction, particularly with their careers, at the same time they continue to experience gender-based inequities, role challenges, and lack of work–life balance in their chosen specialty fields. Lack of suitable role models and appropriate mentoring for women physicians, in addition to barriers to career advancement, are also prevalent across different medical specialties. Conclusion: Similar to other occupations and industries, gender-based inequities and role strains are very real issues for women physicians. Health care organizations must acknowledge these issues and employ effective talent management strategies aimed at women doctors if they are to be viewed as an employer of choice by this increasingly important occupational cohort.